2021
DOI: 10.1038/s41598-020-80465-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Actaea racemosa L. (black cohosh) from some of its potential adulterants using qPCR and dPCR methods

Abstract: The demand for popular natural health products (NHPs) such as Black Cohosh is increasing considerably, which in turn challenges quality assurance (QA) throughout the supply chain. To detect and quantify the target species present in a given NHP, DNA-based molecular techniques such as Real-time quantitative PCR (qPCR) and digital PCR (dPCR) are standard tools in the food and pathogen testing industries. There is a gap in the literature concerning validated quantitative PCR methods for botanicals that can be uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…It would be straightforward to develop similar techniques for the identification of herbs. Recent researches demonstrated that quantification and semi-quantification of target species are possible by different molecular techniques, such as qPCR [ 12 , 13 ], dPCR [ 14 ], vector control quantitative analysis [ 15 ] and double peak detection in nucleotide signature [ 16 , 17 ], further expanding the scope of potential applications of this approach. However, species-specific assays cannot be used to identify unknown samples with no intended target species.…”
Section: Introductionmentioning
confidence: 99%
“…It would be straightforward to develop similar techniques for the identification of herbs. Recent researches demonstrated that quantification and semi-quantification of target species are possible by different molecular techniques, such as qPCR [ 12 , 13 ], dPCR [ 14 ], vector control quantitative analysis [ 15 ] and double peak detection in nucleotide signature [ 16 , 17 ], further expanding the scope of potential applications of this approach. However, species-specific assays cannot be used to identify unknown samples with no intended target species.…”
Section: Introductionmentioning
confidence: 99%
“…The world of eukaryotic DNA-based species identification in food and dietary supplements products has undergone a revolution in the past 10 years, and while progress has been swift it has not been without challenges [8][9][10]. Contemporary methods of DNAbased identification include DNA fingerprinting techniques like restriction fragment length polymorphisms [11], microarrays [12], a full suite of polymerase chain reaction (PCR) methods, [13][14][15][16][17], in addition to traditional DNA barcoding [9,18] and a variety of next generation sequencing (NGS) approaches [19][20][21].…”
Section: Introductionmentioning
confidence: 99%